Determinan Nilai Perusahaan Pada Subsektor Makanan Dan Minuman Periode 2016-2018 - Glory, Jessica Bintang; Yetty, Fitri; Triwahyuningtyas, Nunuk (Jurnal Ilmiah Manajemen Kesatuan, 2020)
The purpose of this research is to examine the influence of capital structure with the calculation of Debt Equity Ratio (DER), Profitability with the proxy of Return On Equity (ROE) and Company Size with the proxy of Size calculations on the company's value with the calculation of Price Book Value (PBV) of the company's food and beverage subsectors listed on the Indonesia Stock Exchange. The data used is secondary data with a sample collection method using purposive sampling. Where the population of this study used is the food and beverage subsectors company listed on the Indonesia Stock exchange with a period of observation 2016 – 2018, with the final samples of research 12 companies selected. Data analysis techniques are conducted using descriptive statistics and data regression analysis panels with the help of E-Views version 10 and Microsoft Excel applications 2013. The results of the research are partially known that the company structure (DER) affects on the company's value (PBV), profitability (ROE) affects the company’s value and the Company Size has no effects to the company's value. As well as independent variables explain the dependent variable by 91.76% Keywords: Capital Structure, Profitability, Company Size and Company Value